ENGARUH NILAI TUKAR RUPIAH TERHADAP TINGKAT SUKU BUNGA PASAR UANG ANTAR BANK (PUAB) DI INDONESIA PERIODE 1991-2005 - Imam Akbar (Department of Development Economics, Universitas Sriwijaya, 2008)
The purposed of this research is to analyze the effect between exchange rate and interbank call money rate in Indonesia the period 1991 up to 2005. The outcame of this research was hoped become the information that could explain the effect of exchange rate against interbank call money rate in Indonesia the period 1991-2005. The data used in this research is secondary data that came from the various source, among them the Statistical Centre Committee the Palembang Branch, The Indonesian Bank, and any literature and books. The result shows that the effect the exchange rate is negative and significant on interbank call money rate.. Key Words: exchange rate and interbank call money rate